2013
DOI: 10.1523/jneurosci.3506-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Epilepsy-Related LGI1 in Limbic Encephalitis Neutralize LGI1-ADAM22 Interaction and Reduce Synaptic AMPA Receptors

Abstract: More than 30 mutations in LGI1, a secreted neuronal protein, have been reported with autosomal dominant lateral temporal lobe epilepsy (ADLTE). Although LGI1 haploinsufficiency is thought to cause ADLTE, the underlying molecular mechanism that results in abnormal brain excitability remains mysterious. Here, we focused on a mode of action of LGI1 autoantibodies associated with limbic encephalitis (LE), which is one of acquired epileptic disorders characterized by subacute onset of amnesia and seizures. We compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
279
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(295 citation statements)
references
References 46 publications
11
279
0
5
Order By: Relevance
“…Our results support and extend reports of enhanced excitatory transmission in Lgi1 −/− mice (7,21). It is possible that conflicting evidence, suggesting reduced AMPA receptor function in Lgi1 −/− mice (6,22,23), may be the consequence of homeostatic synaptic responses to increased excitatory transmission.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results support and extend reports of enhanced excitatory transmission in Lgi1 −/− mice (7,21). It is possible that conflicting evidence, suggesting reduced AMPA receptor function in Lgi1 −/− mice (6,22,23), may be the consequence of homeostatic synaptic responses to increased excitatory transmission.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of glutamatergic neurotransmission in hippocampal slices from Lgi1 −/− mice has yielded conflicting evidence, as both enhanced excitatory transmission (7,21) and reduced AMPA receptor function (6,22,23) have been reported.…”
mentioning
confidence: 99%
“…Patients with limbic encephalitis (LE) develop adult-onset epilepsy and neuropsychiatric symptoms, such as memory deficits and psychosis (43). Research into the mechanism of action of autoantibodies has shown that antibodies isolated from LE patients target LGI1, disrupting the LGI1-ADAM22 interaction and reducing synaptic AMPARs (44). So, whereas it may be that the epilepsy phenotype related to mutations in LGI1 is a result of improper neurite development, it is certain that disruption of the LGI1-ADAM complex in the mature adult brain can also produce disease, indicating a critical function for this complex in synaptic maintenance as well as development.…”
Section: Discussionmentioning
confidence: 99%
“…LGI1 is thought to interact presynaptically with the VGKC complex and postsynaptically with α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR), and the antibodies also reduce AMPAR expression in vitro [55]. Other forms of limbic encephalitis in adults with antibodies to the VGKC complex protein contactin-associated protein 2, γ-aminobutyric acid (b) receptor , or AMPAR may not be clinically distinguishable from this form of limbic encephalitis at presentation but can now be identified by specific antibody tests and are associated with tumors.…”
Section: Antibodies To Identified Cns Proteinsmentioning
confidence: 99%